SISTEM KELAYAKAN INVESTASI REAL ESTATE PADA PERUMAHAN CITRA GARDEN - Hanifah Dwi Nirwana (Lambung Mangkurat University Press, 2019)
Real estate. A review of market, legal, technical and environmental and financial aspects is an important part of determining investment viability. The sequence of processes in conducting a study of these aspects is mostly not done by the developer systematically, so it requires a relatively long time. To facilitate developers in conducting studies on the feasibility of real estate investment, a series of procedures that are systematic and integrated into a system need to be made. The real estate investment feasibility system (SKIR) compiled in this study is limited to middle to upper scale housing located in the city of Banjarmasin and its surroundings. This system is realized into a computerized environment, with the hope that the process of conducting a feasibility study will be more effective. The results of this study are in the form of Real Estate Investment System Application Program. This system uses the Windaw XP operating system with the Microsoft Visual Foxpro 9.0 programming language where the application program can be directly connected to the database. The SKIR program validation was tested with the object of the Citra Garden Housing study with the results of the system running well.